Adaptive Fuelling of the SI Engine - Wendeker, Mirosław (Communications - Scientific letters of the University of Zilina, 2004)
The paper presents some investigations concerning implementation of the adaptive control methods for the control of the fuel injection in an automotive gasoline engine. As quality index the difference between a current emission level and the level obtained during the stoichiometric combustion was chosen. Stoichiometric mixture provides maximal conversion ratio of the catalytic converter. The paper presents mathematical procedures of the direct adaptive control, based on the adaptive algorithms, which use competitive estimators. Theoretical analysis was supplied with the results of computer simulation of the single point gasoline injection engine model.